1997
DOI: 10.1038/bjc.1997.407
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of bioreductive drug toxicity in murine tumours by inhibition of the activity of nitric oxide synthase

Abstract: Summary Nitro-L-arginine inhibits the production of nitric oxide and can thereby cause vasoconstriction in vivo. One consequence of this is that nitro-L-arginine can increase hypoxia in a range of transplantable and spontaneous murine solid tumours. Bioreductive drugs such as RB6145 are more active under hypoxic conditions, and the combination of RB6145 with nitro-L-arginine in vivo shows greater anti-tumour activity than either agent individually. In mice given nitro-L-arginine at 10 mg kg-' i.p. up to 1 h be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…There are some unexplained data that suggest this effect has occurred in other laboratories. Clonogenic survival studies of hypoxic cytotoxin RB6145 in combination with NOS inhibitor L-NNA found several magnitudes greater cell kill than expected for a hypoxic cytotoxic effect when tumours were excised at 24 h [36], [41]. We propose that a large, irreversible vascular damaging effect by RB6145 combined with NOS inhibition may explain these results.…”
Section: Discussionmentioning
confidence: 73%
“…There are some unexplained data that suggest this effect has occurred in other laboratories. Clonogenic survival studies of hypoxic cytotoxin RB6145 in combination with NOS inhibitor L-NNA found several magnitudes greater cell kill than expected for a hypoxic cytotoxic effect when tumours were excised at 24 h [36], [41]. We propose that a large, irreversible vascular damaging effect by RB6145 combined with NOS inhibition may explain these results.…”
Section: Discussionmentioning
confidence: 73%
“…Nitric oxide synthases can also act as reductases of quinones [85] and other bioreductive drugs, including tirapazamine [86]. (Paradoxically, inhibition of nitric oxide synthase enhanced bioreductive drug toxicity in murine tumours [87], possibly in part through decreasing blood flow and thus inducing hypoxia.) are thermodynamically favourable (i.e.…”
Section: Redox Properties Of Some Typical Reductases and Of Oxygen Qmentioning
confidence: 99%
“…Hypoxic tumor cells can be up to 3 times more resistant to radiation than their oxic counterparts [1]. Attempts to improve the efficacy of radiotherapy and chemotherapy by modifying tumor oxygenation has been an area of active research for many years [2–5]. Indeed, as early as 1930 Fischer‐Wasels [6] was using carbogen breathing during radiotherapy to improve tumor oxygenation and radiation response in cancer patients.…”
Section: Introductionmentioning
confidence: 99%